2004
DOI: 10.1148/rg.246035225
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Melanoma: An Unusual Diagnosis for a Large Anterior Mediastinal Mass

Abstract: A 52-year-old woman presented with a nonproductive cough, mild dyspnea, and chest pain. The patient's medical history was significant for melanoma diagnosed in 1986. The melanoma was localized to the upper left side of her back and was treated with surgical resection. Otherwise, the patient's surgical history and medical history were unremarkable. Her family medical history was significant for lymphoma (mother) and colon cancer (sister). The patient smoked 1.5 packs of cigarettes a day for 20 years.The patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…One case was misdiagnosed as a spindle cell thymoma due to the spindle cell morphology, lack of thoracic lesion, and lack of cutaneous melanoma history . Others reported case present with a past history of documented cutaneous melanoma . Each of these case reports reveals the importance of keeping metastatic melanoma in the differential diagnosis when evaluating mediastinal masses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One case was misdiagnosed as a spindle cell thymoma due to the spindle cell morphology, lack of thoracic lesion, and lack of cutaneous melanoma history . Others reported case present with a past history of documented cutaneous melanoma . Each of these case reports reveals the importance of keeping metastatic melanoma in the differential diagnosis when evaluating mediastinal masses.…”
Section: Discussionmentioning
confidence: 99%
“…13 Others reported case present with a past history of documented cutaneous melanoma. 15,16 Each of these case reports reveals the importance of keeping metastatic melanoma in the differential diagnosis when evaluating mediastinal masses.…”
Section: Discussionmentioning
confidence: 99%
“…13 Single-agent chemotherapy with dacarbazine has proved ineffective, with a response rate of only 10–20% in the treatment of metastatic melanoma. 14 Systemic chemotherapy and immunotherapy are sometimes used to treat advanced disease. 4 One study reported a slightly improved response rate for combination chemotherapy with interferon alpha-2b and interleukin-2 in the treatment of metastatic melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…4 One study reported a slightly improved response rate for combination chemotherapy with interferon alpha-2b and interleukin-2 in the treatment of metastatic melanoma. 14 Temozolomide may also be used in combination with interferon alpha-2b. 1 Dabrafenib and trametinib are approved for use as monotherapy but with intracranial haemorrhage as a potential side effect.…”
Section: Discussionmentioning
confidence: 99%
“…This includes leukemia, lymphoma, choriocarcinoma, angiosarcoma, and adenocarcinona [ 11 , 12 ]. Metastatic melanoma commonly involves lung as an endobronchial mass, solitary or multiple pulmonary nodules, hilar or mediastinal lymphadenopathy and pleural effusion [ 13 ]. The patchy infiltrative or ground glass metastatic pattern, mimicking pulmonary edema or pneumonitis is unusual.…”
Section: Discussionmentioning
confidence: 99%